Goiânia através dos espaços públicos: praças e parques como fator de segregação - Vieira, Gabriela Cavalcante Lemos (2020)
Public spaces have been adapting over the years according to the transformations that have taken place in the city, taking on various forms of appropriation and moving through different meanings and concepts. Since the late 1980s, there has been an influx of research on the decline of public spaces, due to numerous reasons. In Goiânia, there is such a decline in relationships such as: the overvaluation of urban land, urban segregation, the absence of basic infrastructure in the countless approved subdivisions, the new forms of work relationship (and not work), the prioritization of the use of transportation motorized and the technological revolution of communication. According to David Harvey (2014) cities have become places to invest and not to live, the well-being of the population is no longer a priority, while profit has become the main concern in urban development. Currently, the transformation of the city's landscape is based on the interplay of interests between public and private powers, and concentrates investments in strategic areas for them. The choice of public leisure spaces (squares and parks) in Goiânia as an object of study stems from the need to point out the inefficiency of the public authorities in guaranteeing these spaces for the majority of the population residing in the city, in sprawling and deprived regions of the capital. This work deals with public facilities in poor neighborhoods (usually peripheral), as opposed to areas of greater purchasing power, seeking to unveil the real priorities of public policies and the imbalances in the application of resources, highlighting those related to the right to the city and urban infrastructure. leisure in the capital. Urban inequalities must be highlighted in order to seek improvements, making regions neglected by public and private powers more dignified. It is imperative to make this urban problem visible, which is reflected in the daily lives of people deprived of spaces where they can exercise their citizenship, that is, live together, interact, enjoy, exchange ideas and share experiences. When establishing comparisons between public facilities in poor neighborhoods with areas of greater purchasing power, indicating the regions of Goiânia benefited or not with the implementation of quality public leisure spaces, we highlight the factors of social and territorial segregation. We chose to include in the research everyday experiences of visitors to these areas, in an attempt to broaden the perception of a serious urban problem investigated by methodological processes are of an applied and explanatory nature, also evidenced in quantitative, qualitative and investigative analyzes. The research covered populous neighborhoods in the central, east, northwest, north, west, southwest and south of Goiânia administrative regions, implemented in different periods, and points out possible factors that imbalance public and private investments, real estate speculation and territorial and social segregation. Public leisure spaces - squares and parks - are analyzed by means of maps, tables and images of the aspects raised, as well as reports of residents' lives, proposing an approach under the right to the city